Bone crossed - Briggs, Patricia (New York : Ace Books, 2009)
By day, Mercy Thompson is a car mechanic. By night, she explores her preternatural side and finds herself maintaining a tenuous harmony between the human and the not-so-human world of witches, vampires, werewolves and shape-shifters populating Eastern Washington.
Keywords: Thompson, Mercy (Fictitious character) -- Fiction; Automobile mechanics -- Fiction; Metamorphosis -- Fiction; Vampires -- Fiction; Werewolves -- Fiction; Fantasy fiction; Occult fiction